2018 IEEE Energy Conversion Congress and Exposition (ECCE) 2018
DOI: 10.1109/ecce.2018.8557531
|View full text |Cite
|
Sign up to set email alerts
|

Stretching in Time of GaN Active Gate Driving Profiles to Adapt to Changing Load Current

Abstract: Active gate driving, where the gate signal is actively profiled, has been shown to reduce EMI, overshoot, and switching loss, in silicon power converters. Recently, much faster gate drivers with the ability to profile at a 100 ps resolution have been reported, which has opened up the possibility of actively driving emerging wide-bandgap devices. This could allow Gallium Nitride (GaN) and Silicon Carbide (SiC) FETs to be switched faster than is currently possible, as unwanted switching features such as current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…More precisely, variations of the load current should be careful considered, as they are rather common in practical scenarios. Reference [8] suggests to reduce the clock frequency of the proposed AGD when the load current increases. In [7], both current and temperature variations were investigated, and, a look-up table is proposed to store the AGD profiles for different currents in [9].…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, variations of the load current should be careful considered, as they are rather common in practical scenarios. Reference [8] suggests to reduce the clock frequency of the proposed AGD when the load current increases. In [7], both current and temperature variations were investigated, and, a look-up table is proposed to store the AGD profiles for different currents in [9].…”
Section: Introductionmentioning
confidence: 99%
“…Driving an e ‐mode GaN transistor is similar to driving an n‐type silicon power MOSFET but with new challenges. The low threshold voltage (around 1.5 V) and low maximum gate voltage (7 V) narrow the tolerance of safe gate driving voltage window [7], which restricts the maximum d ν /d t and d i /d t due to possible ringing during the turn‐on and turn‐off transitions [8, 9]. The lack of an integrated body diode also leads to large undershoot voltage which increases reverse conduction loss.…”
Section: Introductionmentioning
confidence: 99%
“…The fact of high computation cost and time consuming is also reported in [19] when automatic optimization based on simulated annealing was applied. A similar issue in determining the gate drive profile was also addressed in [20]- [22]. A systematic approach to demonstrate the effect of digital active gate drive waveforms on an IGBT switching operation was proposed in [20].…”
mentioning
confidence: 99%
“…In [21], the searching time for the optimum gate resistor values is reduced because of less experimental tests, which were followed by an analysis of the measured waveforms and losses. In [22], a profiled optimum gate drive waveform is able to adapt to load current variations using driver frequency adaption. Moreover, [23] reported that the resulting optimal pattern is dependent on circuit stray inductance.…”
mentioning
confidence: 99%